Structural and Functional Features of the P2X4 Receptor: An Immunological Perspective - Kanellopoulos, Jean M.; Almeida-da-Silva, Cássio Luiz Coutinho; Rüütel Boudinot, Sirje; Ojcius, David M. (Frontiers in Immunology, 2021)
Extracellular nucleotides are important mediators of activation, triggering various responses through plasma membrane P2 and P1 receptors. P2 receptors are further subdivided into ionotropic P2X receptors and G protein-coupled P2Y receptors. P2X4 is an ATP-gated cation channel broadly expressed in most tissues of the body. Within the P2X family, P2X4 has a unique subcellular distribution, being preferentially localized in lysosomes. In these organelles, high ATP concentrations do not trigger P2X4 because of the low pH. However, when the pH increases to 7.4, P2X4 can be stimulated by intra-lysosomal ATP, which is in its active, tetra-anionic form. Elucidation of P2X4, P2X3 and P2X7 structures has shed some light on the functional differences between these purinergic receptors. The potential interaction between P2X4 and P2X7 has been extensively studied. Despite intensive effort, it has not been possible yet to determine whether P2X4 and P2X7 interact as heterotrimers or homotrimers at the plasma membrane. However, several publications have shown that functional interactions between P2X4 and P2X7 do occur. Importantly, these studies indicate that P2X4 potentiates P2X7-dependent activation of inflammasomes, leading to increased release of IL-1 and IL-18. The role of P2X4 in various diseases could be beneficial or deleterious even though the pathophysiological mechanisms involved are still poorly defined. However, in diseases whose physiopathology involves activation of the NLRP3 inflammasome, P2X4 was found to exacerbate severity of disease. The recent production of monoclonal antibodies specific for the human and mouse P2X4, some of which are endowed with agonist or antagonist properties, raises the possibility that they could be used therapeutically. Analysis of single nucleotide polymorphisms of the human P2RX4 gene have uncovered the association of P2RX4 gene variants with susceptibility to several human diseases.